ROCK2 regulates autophagy in the hippocampus of rats after subarachnoid hemorrhage. Issue 18 (12th December 2018) - Sun, Linlin; Ma, Yude; Zhang, Zhiyong; Li, Xiaoliang; Chen, Yang; Liu, Gang; Fu, Aijun
Abstract : The role of autophagy in subarachnoid hemorrhage (SAH) remains unclear. This study aimed to investigate the role of ROCK2 in the regulation of hippocampus autophagy after SAH. Thirty-six Sprague-Dawley rats were randomly divided into three groups – the sham group, the SAH group, and the SAH+ ROCK2 inhibitor group (or the drug group) – and analyzed through a behavior test. The hippocampus tissues were analyzed using immunochemistry and western blot analysis. We observed injured morphology in the hippocampus and impaired learning and memory ability in the rats in the SAH group, accompanied by upregulated ROCK2 expression and increased beclin-1 and LC3-II expression. Compared with the SAH group, we observed normal morphology in the hippocampus and better learning and memory ability in the rats in the drug group, accompanied by downregulated ROCK2 expression and increased beclin-1 and LC3-II expression. SAH activates autophagy in the hippocampus, but this could be inhibited by ROCK2. Inhibition of ROCK2 promotes autophagy and reduces the injury in the hippocampus, leading to the recovery of learning and memory ability following SAH. ROCK2 may represent a new target for the treatment of SAH.